Strategic interactions and price dynamics in the global oil market - Irma Alonso Alvarez; Virginia Di Nino; Fabrizio Venditti (European Central Bank (ECB), 2020)
In a simplified theoretical framework we model the strategic interactions between OPEC and non-OPEC producers and the implications for the global oil market. Depending on market conditions, OPEC may find it optimal to act either as a monopolist on the residual demand curve, to move supply in-tandem with non-OPEC, or to offset changes in non-OPEC supply. We evaluate the implications of the model through a Structural Vector Auto Regression (VAR) that separates non-OPEC and OPEC production and allows OPEC to respond to supply increases in non-OPEC countries. This is done by either increasing production (Market Share Targeting) or by reducing it (Price Targeting). We find that Price Targeting shocks absorb half of the uctuations in oil prices, which have left unexplained by a simpler model (where strategic interactions are not taken into account). Price Targeting shocks, ignored by previous studies, explain around 10 percent of oil price uctuations and are particularly relevant in the commodity price boom of the 2000s. We confirm that the fall in oil prices at the end of 2014 was triggered by an attempt of OPEC to regain market shares. We also find the OPEC elasticity of supply three times as high as that of non-OPEC producers.
Keywords: Q41; Q43; 330; OPEC; shale; oil; VAR